Measuring the Performance and Achievement of Social Objectives of Development Finance Institutions - Francisco, Manuela; Mascaró, Yira; Mendoza, Juan Carlos; Yaron, Jacob (World Bank, Washington, DC, 2012)
This paper develops and tests a proposed methodology that puts forward a new integrated method for evaluating the performance of development finance institutions. This methodology applies assessment criteria that take into account both the social objective that the development finance institution addresses and the subsidies it received in order to achieve such an objective. This methodology is applied to two pilot case studies-Banadesa (Honduras) and Banrural (Guatemala). The authors calculate the previously tested subsidy dependence index, which measures the degree of an institution's subsidy dependence. The paper develops and estimates a new measure-the output index- which indicates the level to which the institution fulfills the social objectives of the state. The analysis integrates the subsidy dependence index and the output index to assess the effectiveness associated with meeting the social objective. The findings suggest that the integration of the two indexes can constitute the basis of a meaningful evaluation framework for the performance of development finance institutions. This new methodology can also be a useful metric for policy makers who are seeking to decide on an optimal allocation of scarce funds for development finance institutions that pursue social goals and for management that seeks improved performance outcomes.